Privacy preserving proof of ownership for data in cloud storage systems - Tirapathi Reddy, B; V. P. Chandra Sekhara Rao, M (International Journal of Engineering and Technology, 2018)
Storing data in cloud has become a necessity as users are accumulating abundant data every day and they are running out of physical storage devices. But majority of the data in the cloud storage is redundant. Data deduplication using convergent key encryption has been the mechanism popularly used to eliminate redundant data items in the cloud storage. Convergent key encryption suffers from various drawbacks. For instance, if data items are deduplicated based on convergent key, any unauthorized user can compromise the cloud storage by simply having a guessed hash of the file. So, ensuring the ownership of the data items is essential to protect the data items. As cukoo filter offers the minimum false positive rate, with minimal space overhead our mechanism has provided the proof of ownership.